Programmable Nanoassemblies from Non-Assembling Homopolymers Using ad hoc Electrostatic Interactions - Zhuang, Jiaming (Angew Chem Int Ed Engl, 2017)
Robust nanostructures have been obtained from otherwise non-assembling polymers using a novel ad hoc electrostatic self-assembly approach. The essence of this strategy involves the use of divalent counterions to temporarily perturb the packing features of ionic groups in a homopolymer, which results in a vesicle-like structure that is captured in situ through a simple crosslinking reaction. The fidelity of the assembly has been tested for molecular transport across the nanomembrane, both for the molecules encapsulated in the lumen and for those trapped in the membrane itself. The membranes are addressable for robust multifunctionalization of their surfaces and for tunable transmembrane molecular transport.